2006
DOI: 10.1007/s00125-006-0194-7
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of adiponectin by human placenta: differential modulation of adiponectin and its receptors by cytokines

Abstract: Aims/hypothesis: Pregnancy, a state of insulin resistance, is associated with elevated levels of cytokines and profound alterations in metabolism. Serum adiponectin, an adipokine with anti-inflammatory and insulinsensitising properties, has been shown to be lower in patients with gestational diabetes mellitus, a state of greater insulin resistance than normal pregnancies. Hypothesising that the human placenta is a source of adiponectin, we investigated its expression and secretion, and the regulation by cytoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
177
4
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(197 citation statements)
references
References 40 publications
10
177
4
6
Order By: Relevance
“…While the presence of syncytiotrophoblast adiponectin expression has been previously debated,39, 40 the present study demonstrated adiponectin expression in both syncytiotrophoblasts and decidual glands. In the in vitro model cell experiments, we also found that adiponectin was expressed in syncytial BeWo cells.…”
Section: Discussionsupporting
confidence: 50%
“…While the presence of syncytiotrophoblast adiponectin expression has been previously debated,39, 40 the present study demonstrated adiponectin expression in both syncytiotrophoblasts and decidual glands. In the in vitro model cell experiments, we also found that adiponectin was expressed in syncytial BeWo cells.…”
Section: Discussionsupporting
confidence: 50%
“…28 Approximately, the same rate of release was seen by cut pieces of adipose tissue that did not contain enough lipid to float. 28 The view that the expression of adiponectin mRNA is restricted to mature adipocytes is clearly untenable in view of the present findings and the recent reports that adiponectin is synthesized and secreted by human osteoblasts, 10 human cardiomyocytes, 11 murine skeletal muscle, 12 human skeletal muscle and placenta, 13 human liver biopsies, 14 human placental synctiotrophoblasts, 15 as well as human fetal tissues of both mesodermal and ectodermal origin. 16 The present data using omental adipose tissue explants confirm the prior reports by Matsuzawa's laboratory that adiponectin release is reduced by obesity 4 as well as diabetes.…”
Section: Discussionmentioning
confidence: 69%
“…7,8 Adiponectin was originally described as an adipocytespecific protein. [1][2][3] However, more recently adiponectin mRNA and secretion have been demonstrated in boneforming cells, 9,10 cardiomyocytes, 11 skeletal muscle, 12,13 human liver, 14 human placental syncytiotrophoblasts 15 and human fetal tissues of mesodermic and ectodermal origin. 16 It is unclear whether tissues other than adipose tissue contribute to circulating levels of adiponectin that are some 40-fold higher than those of leptin in obese subjects.…”
Section: Introductionmentioning
confidence: 99%
“…A few in vitro studies have shown either no relation between leptin and adiponectin gene expression or indeed a negative correlation, 27,28 but upregulation of adiponectin gene expression by leptin has been also hypothesized. 6 In our subjects leptin levels were significantly associated with both HOMA and waist circumference whereas the association between leptin and adiponectin gene expression appeared only after adjusting for waist (r ¼ 0.48, P ¼ 0.016).…”
Section: Adiponectin Gene Expression In Human Adipocytes M Zamboni Et Almentioning
confidence: 99%